Autoimmune Hypothyroidism As a Predictor of Mortality in Chronic Hypersensitivity Pneumonitis - Adegunsoye, Ayodeji; Oldham, Justin M.; Husain, Aliya N.; Chen, Lena; Hsu, Scully; Montner, Steven; Chung, Jonathan H.; Vij, Rekha; Noth, Imre; Strek, Mary E. (Frontiers in Medicine, 2017)
Background Chronic hypersensitivity pneumonitis (CHP) is a fibrotic parenchymal lung disease that occurs when inhalation of environmental antigens leads to immune dysregulation. Autoimmune features have recently been identified as potentially important among patients with CHP. However, the relationship between hypothyroidism (HT) and CHP is unknown. In this study, we investigate the prevalence and impact of HT among patients with CHP. Methods We conducted a retrospective, case-control analysis. We identified 121 patients at the University of Chicago Interstitial Lung Disease Center with a multi-disciplinary diagnosis of CHP. These patients were matched 3:1 according to age, sex, and race, to 363 control subjects with asthma from 2006–2015. We analyzed demographics, clinical characteristics, and survival between both groups and assessed the relationship of HT with CHP. Survival analysis was performed using Cox proportional hazards modeling. Results Patients with CHP had higher prevalence of HT (25.6%, n=31) compared to controls (10.7%, n=39; OR, 2.86; 95% CI, 1.62-4.99; P<0.0001). Compared to CHP alone, patients with CHP/HT were more likely to be female (80.6% vs 51.1%, P=0.004), have increased incidence of autoimmune disease (19.4% vs 3.3%, P=0.009), antinuclear antibody seropositivity (80.6% vs 57.0%, P=0.019), and higher TSH levels (4.0mIU/L vs 1.9mIU/L, P<0.0001). HT was a significant independent predictor of mortality among CHP patients with seropositive ANA (HR, 3.39; 95% CI, 1.31-8.80; P=0.012). Conclusions HT is common in patients with CHP and may carry prognostic significance in patients with features of autoimmunity. Further research exploring common pathogenic pathways between autoimmune HT and CHP may illuminate the association of HT with survival.